Spillover of sustainable routines from work to private life: application of the Identity and Practice Interdependence Framework - Frezza, Marcia (Frontiers in Psychology, 2024)
Introduction: Spillover of sustainable routines and environmentally-responsible behaviors from one setting to another may contribute to achieving essential sustainability goals. Several previous studies on this topic have found few examples of spillover and have focused primarily on individual influences, indicating the need for a better understanding of the factors that have an impact on whether, how, and when spillover occurs. To this end, a novel conceptualization examining the interactions between identity principles and socio-material elements, the Identity and Practice Interdependence Framework, was applied to investigate the occurrence of spillover of sustainable routines from the workplace to home.Methods: Three focus groups totaling thirty employees of a major Brazilian steel-producing company, interviews in fifteen employee homes, and on-site observations of work and private domains provided data that was analyzed qualitatively, using a deductive reflexive thematic approach.Results: Participants identified 58 changes in home routines related to sustainability as resulting from their experiences at work. With the consistent availability of practice elements (materials, competencies, meanings), learning about, witnessing and performing sustainable routines at work favored satisfactory levels of identity principles (self-efficacy, self-esteem, distinctiveness, continuity). Analysis suggested that seeking the same satisfactions of identity principles outside the workplace led individuals to adapt, change, and/or create more environmentally-responsible routines in their homes.Discussion: The Identity and Practice Interdependence Framework permitted investigation of the integration of socio-material aspects with the role of individuals in the process of spillover, and indicated some ways they may interact. Both the provision of socio-material components in the first setting and the recognition of more sustainable routines as a feasible path to satisfaction of identity principle needs contribute to individual engagement and persistence in the second setting. Consistent and frequent experiences with more sustainable routines in the first setting or situation may be key to creating this expectation, and therefore to the occurrence of spillover to another setting. The framework complements previous approaches by allowing for a more complex analysis of spillover, which can be used to enrich research on sustainable practices and help promote environmentallyfriendly behaviors and sustainable routines both within organizations and beyond.